Keberagaman Dewan Direksi dan Kinerja Keuangan: Bukti dari Sektor Manufaktur Indonesia - Muharrom Firmansyah; Ajeng Tita Nawangsari; Bima Rafly Fachrezzi (Jurnal Kajian Akuntansi, 2026)
Financial performance is a crucial topic in research as it serves as a key indicator for investors, creditors, and internal corporate stakeholders. By evaluating financial performance, investors and creditors can assess risks, while management can utilize the insights to refine corporate strategies and policies. This study aims to analyze the influence of board diversity on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. This research employs a quantitative approach using secondary data obtained from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sample consists of 116 companies, selected using the purposive sampling method. Panel data is analyzed using Eviews 12 software and multiple regression analysis, complemented by the Chow and Hausman specification tests. The findings indicate that gender diversity has a significant influence on financial performance, whereas age diversity, nationality diversity, and educational diversity do not exhibit a significant effect. This study provides recommendations for corporate management to pay greater attention to board composition, particularly regarding gender diversity, given its positive and significant impact on financial performance. Management is encouraged to foster an inclusive work environment and ensure equal opportunities for all board members in strategic decision-making processes. Furthermore, companies are advised to enhance transparency in financial performance reporting to build investor and stakeholder trust. By implementing sound corporate governance policies and optimizing board diversity, firms can enhance their competitiveness and long-term business sustainability.